The impact of human immunodeficiency virus coinfection on mpox patients during the 2022 global outbreak: a systematic review and meta-analysis based on comparative observational studies - Han, Yingying; Li, Xingzhao; Wang, Xin; Zhong, Zhuan (Frontiers in Microbiology, 2026)
BackgroundThe mpox outbreak in 2022 posed a new challenge to the medical system. We aimed to study the impact of human immunodeficiency virus (HIV) coinfection on mpox patients.MethodsThis study was conducted in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines.ResultsOur study included 27 articles for meta-analysis and divided mpox patients into two groups: one group was HIV-positive, and the other group was HIV-negative. We found that the age of HIV-positive patients was significantly greater than that of HIV-negative patients (SMD = 0.35, 95% CI: 0.29–0.41) and that there were more men who had sex with men in the HIV-positive group (OR = 3.98, 95% CI: 3.04–5.21). Syphilis (OR = 2.66, 95% CI: 2.13–3.33), hepatitis B (OR = 3.94, 95% CI: 2.93–5.30), hepatitis C (OR = 5.71, 95% CI: 3.06–10.64), proctitis (OR = 1.52, 95% CI: 1.17–1.98), fever (OR = 1.15, 95% CI: 1.01–1.30), diarrhea (OR = 1.69, 95% CI: 1.03–2.77) and pustules (OR = 1.33, 95% CI: 1.08–1.62) were more common among HIV-positive patients. HIV coinfection seemed to be associated with a decrease in the CD4+ T-cell count (SMD = −0.78, 95% CI: −1.34 to −0.23) and hemoglobin (SMD = −0.43, 95% CI: −0.64 to −0.22) and albumin (SMD = −0.35, 95% CI: −0.55 to −0.15) levels, whereas the CD8+ T-cell count yielded the opposite statistical conclusion (SMD = 0.35, 95% CI: 0.03–0.67). We also found that HIV-positive patients had more hospitalizations (OR = 1.63, 95% CI: 1.22–2.19), more severe mpox (OR = 1.82, 95% CI: 1.28–2.58), more need for tecovirimat treatment (OR = 4.25, 95% CI: 1.59–11.4), and higher mortality (OR = 3.36, 95% CI: 1.15–9.83).ConclusionOverall, HIV coinfection may influence the disease process and clinical indicators of mpox patients and is associated with more severe clinical outcomes.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD420251056729, PROSPERO registration number: CRD420251056729.